Identification and genetic diversity of two human parvovirus B19 genotype 3 subtypes - Parsyan, Armen; Szmaragd, Camille; Allain, Jean-Pierre; Candotti, Daniel (Journal of general virology, 2007)
Three genotypes (1-3) of human parvovirus B19 have been identified. Analysis of 13 nearly full-length genotype 3 sequences from Ghana, Europe and Brazil identified two genetically distinct clusters. The classification of genotype 3 strains into two subtypes (B19/3a and B19/3b) is proposed. The rate of evolutionary change of B19 genotype 3 strains (2 x 10(-4) nucleotide substitutions per site per year) was similar to those of B19 genotype 1 and carnivore parvoviruses, supporting the hypothesis that high mutation rates are characteristic of members of the family Parvoviridae. The estimated divergence time between B19/3a and B19/3b is 525 years. In Ghana, subtype B19/3a is predominant.